Quantum Darwinism and Friends - Deffner, Sebastian; Laflamme, Raymond; Paz, Juan Pablo; Zwolak, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In honor of Wojciech Zurek's 70th birthday, this Special Issue is dedicated to recent advances in our understanding the emergence of classical reality, and pays tribute to Zurek's seminal contributions to our understanding of the Universe. To this end, "Quantum Darwinism and Friends" collects articles that make sense of the apparent chasm between quantum weirdness and classical perception, and provides a snapshot of this fundamental, exciting, and vivid field of theoretical physics.